Knowledge and Misconceptions About Diabetes Mellitus in Semarang: An In-Depth Survey Analyzing the Impact of Public Awareness on Prevention and Management - Wilson Setiawan, Andreas; Rahel Konoralma, Amanda; Anggraini, Tyas; Melki; Maya Chandra Khodijah, Ira; Ratna Wulan, Widya (Health Science UDINUS, 2024)
Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia resulting from impaired insulin secretion, insulin action, or both. According to the IDF data, in 2021, there were 537 million people with diabetes globally, with more than 70% of them undiagnosed. In Semarang City, in 2023, there were 41,468 reported cases of diabetes, with the majority in the age group of 46-65 years. Public knowledge about diabetes, including its symptoms, risk factors, prevention, and management, is crucial to combat this disease. This research employed a descriptive-analytic epidemiological method with a Rapid Survey design. Data was collected in November 2024 at the Pramita Laboratory in South Semarang. The study population consisted of participants from a health education program themed